Bases de un sistema de gestión de calidad para un centro de técnicas de reproducción asistida The basis for a quality management system for an assisted reproduction technique centre - Jaime Saavedra-Saavedra (Federación Colombiana de Obstetricia y Ginecología, 2006)
El propósito de este informe es revisar aquellos factores que se deberían considerar en la evaluación de calidad total de un centro de técnicas de reproducción asistida. Metodología: se revisan las definiciones de calidad, gestión de calidad y calidad en centros de reproducción. Se revisa la percepción del cliente sobre calidad en estos centros y se describen los indicadores aceptados por las entidades internacionales de la subespecialidad. Resultados: se hace una aproximación crítica a estos indicadores con la descripción de la acreditación de este centro como ejemplo del proceso a seguir, se brindan los indicadores de la entidad. This paper is aimed at examining the factors which should be considered when evaluating an assisted reproduction centre’s overall quality. Normal methods for evaluating quality were reviewed. Many state regulating institutions around the world have become centred just on pregnancy rates, which could lead to erroneous conclusions if other essential factors are not taken in count, such as multiple pregnancy, ovarian hyper-stimulation, customer satisfaction, suitable laboratory evaluation and applying clinical protocols. This article describes how our institution was accredited as a model for such process. Methods and procedures for improving quality are essential in all business models, including those pertaining to assisted reproduction centres. ISO 9001 is applied in our institution when evaluating and improving the service provided for our patients.